Stability Indicating Method Development, Validation and Forced Degradation Study for Vilazodone Hydrochloride API - Chaudhari, Yogesh Jagdish; Lokhande, Rama Sadashiv; Yadav, Ravi Ramrathi (Oriental journal of chemistry, 2021)
The current study describes the short, stability indicative HPLC method development and successive validation of Assay and Related Substances methods for Vilazodone Hydrochloride API. This study also covers Vilazodone process impurities viz. Impurity A and Impurity B. The chromatographic conditions for Related Substances and Assay are similar except sample concentration. The proposed method utilizes C18 column (15 cm X 4.6 mm, 5 µ, make ZORBAX SB) and mobile phase having Methanol and 0.05 M KH2PO4 (55: 45 v/v). The separation between all three analytes was achieved in less than five minutes. The analytical validation of these method was carried out successfully as per ICH and other international guidelines. The API was subject to various stress conditions like temperature, humidity, acidic and basic hydrolysis, oxidative degradation. The exposed samples analysed for impurities and assay. The mass balance for each condition was found more than 98%.